2020
DOI: 10.1093/aje/kwaa245
|View full text |Cite
|
Sign up to set email alerts
|

Racial Disparities in Health Among College-Educated African Americans: Can Attendance at Historically Black Colleges or Universities Reduce the Risk of Metabolic Syndrome in Midlife?

Abstract: We expand on existing understandings of health disparities among middle-class African-Americans by examining how the postsecondary educational context gives rise to the unequal distribution of health. We use panel data (1994-2009) from the National Longitudinal Survey of Adolescent to Adult Health (Add Health) to estimate if the risk of developing metabolic syndrome by midlife significantly differs for African-Americans who attended Historically Black College or Universities (HBCUs) vs. predominantly White ins… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The samples utilized in studies that found effect modification ( Howard & Sparks, 2015 ; Richardson et al, 2021 ; Sims & Coley, 2019 ), however, were either mostly (or solely) comprised of adults who attended school after Brown when access to higher education was greater for Black adults. While more Black adults were able to attend college during the post- Brown era, doing so at predominantly White institutions also increases exposure to racial marginalization and discrimination ( Feagin et al, 1996 ; Lewis & Shah, 2021 ), which has been linked to poorer metabolic health ( Colen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The samples utilized in studies that found effect modification ( Howard & Sparks, 2015 ; Richardson et al, 2021 ; Sims & Coley, 2019 ), however, were either mostly (or solely) comprised of adults who attended school after Brown when access to higher education was greater for Black adults. While more Black adults were able to attend college during the post- Brown era, doing so at predominantly White institutions also increases exposure to racial marginalization and discrimination ( Feagin et al, 1996 ; Lewis & Shah, 2021 ), which has been linked to poorer metabolic health ( Colen et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…shown that attending an HBCU versus a PWI predicted lower risk of metabolic syndrome in mid-life Black adults, and that this effect was strongest for those who attended predominantly Black high schools and lived in predominantly Black communities, 31 but no previous study has evaluated later life cognitive outcomes. Our study findings underscore the need for more nuanced data collection on race-based educational experiences to better understand Black-White inequities in cognitive aging across all levels of educational attainment.…”
Section: Limited Hbcu and Aging-related Health Literaturementioning
confidence: 99%
“…This is due in part to the fact that despite wide availability of large data sources comprised of demographic and health variables, few datasets include the specific names or school codes of colleges attended and subsequent cognitive outcomes. A recent study among Medicaid recipients in Northern Manhattan showed that attending an HBCU versus a PWI provided mid-life Black adults some protection against developing metabolic syndrome, 31 a condition linked to increased progression of dementia, 32,33 suggesting a pathway through which HBCU attendance may protect against cognitive decline for Black adults.…”
Section: Introductionmentioning
confidence: 99%
“…These include greater levels of faculty interactions and a welcoming environment inclusive of racial and cultural diversity, while ensuring positive academic outcomes including less time to degree completion and similar graduation rates as non-HBCUs (Anderson & Hrabowski, 1977;Fountaine, 2012;Hall & Clossen, 2005;Palmer et al, 2012). At least one study indicated that there were health benefits that accrued later in life that are attributable to attending an MSI (Colen et al, 2021). African American graduate students in particular have emphasized the affirming, caring, and nurturing environments of HBCUs in influencing their personal and professional development (Palmer et al, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%